NEW PRAWN GROUND IN THE GULF OF MANNAR - Nair, R V; Nandakumar, G (Indian Journal of Fisheries, 2011)
Since the beginning of the last decade, systematic exploratory surveysto assess the fishery potential of the offshore regions of the Gulf of Mannarw^ere undertaken b-y the Deep Sea Fishing Station, Government of India andthe Indo-NoTwegiaa Project from Tuticorin and Mandapam bases respectively.The results of thesie surveys have revealed certain productive fishing areas forfish and prawns (Bao, 1968; Rao and Dorairaj, 1969; James and Adolf, 1969).Encouraged by these results, entrepreneurs came forward to undertake offshorefishing on a commercial scale and at present there are about 250 mechanisedboats regularly engaged in trawl fishing in the Gulf of Mannar and Palk Bay,with Mandapam, Pamban and Rameswaram as their bases of operation.